Sifat Fisis Tanah Lempung Ekspansif yang Disubstitusi dengan Serbuk Limbah Keramik: Physical Properties of Expansive Clay Substituted with Ceramic Waste Powder - Dewi, Ratna; Idris, Yakni; San, Indra Chusaini; Lien DYN; Putri Tisya R (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2022)
Expansive soils have high compressibility, swelling, and shrinkage properties. So we need an effective method to improve soil conditions when the structure is built on it. This paper presents the results of research on the effect of the substitution of ceramic waste on the physical properties of the expansive soil. Soil improvement using construction waste will contribute to reducing the amount of waste and conserving natural resources. The stages of the research included testing the physical properties of both soil and waste materials, then testing the physical properties of the mixed soil which included the Atterberg limit test, soil compaction test, and SEM test. The addition of ceramic waste powder can function as a material that can chemically change the physical properties of the soil. There was a decrease in the optimum water content (wopt) of the soil and an increase in the maximum dry density (gd max) value of the soil along with the addition of the percentage of ceramic waste powder that was up to 1.410 gr/cm3. The percentage of chemical content (SiO2 and Al2O3) in ceramic powder affects soil compaction parameters and decreases soil plasticity index, where the content of SiO2 and Al2O3 in ceramic powder 1 is higher than ceramic powder 2 giving lower IP (Index Plasticity) values and optimum moisture content, respectively by 16.26 and 28%, and a higher maximum dry density value of 14.4 gr/cm3.